The Green Campus Building's Rooftop Photovoltaic System Design Project - Handoko Rusiana Iskandar; Deri Mardiansyah; Atik Charisma; Een Taryana; Yuda Bakti Zainal (P3M Politeknik Negeri Cilacap, 2024)
Universitas Jenderal Achmad Yani, whose major campus is in Cimahi City, is constructing a large-scale campus development, the size of which is directly proportionate to the quantity of energy consumed. This increase in electrical energy consumption can be minimized by utilizing environmentally friendly renewable energy sources to supply loads and reduce the use of existing energy from the grid (PT. PLN). This context supports a design proposal for the production of photovoltaic-based photovoltaic on the Universitas Jenderal Achmad Yani campus, particularly in two buildings with exceptional roof potential. In this paper, the modeling carried out aims to help supply renewable energy-based electrical energy. The design of PV on Grid Installation Engineering in Buildings at Universitas Jenderal Achmad Yani carried out in this paper includes PV placement layout, PV construction, and simulation using PVsyst. The rooftop-type grid-connected PV is modeled in the Faculty of Health Sciences and Technology (FHST) Building and the Rectorate Building, which are composed of PV panels, inverters, and other supporting components. Grid PV design and simulation modeling on the roofs of FITKES and Rectorate Buildings resulted in a total installable PV capacity of 420 kWp, an annual average Performance Ratio of 80.6%, and an average potential energy output of 702 MWh/year. This energy potential is undoubtedly proposed to fulfill future electricity needs.